Clinical and radiological features of pulmonary artery sarcoma: A report of nine cases. (12th December 2017) - Pu, Xin; Song, Man; Huang, Xiaoyong; Zhu, Guangfa; Chen, Dong; Gan, Huili; Huang, Lianjun
Abstract: Objective: To improve our understanding and facilitate early diagnosis of pulmonary artery sarcoma (PAS). Patients and Methods: The clinical and radiological features of 9 histopathologically confirmed patients with PAS were retrospectively analyzed. Results: Our PAS cohort consisted of 5 males and 4 females, with insidious presentation, the main symptoms were dyspnea (88.9%), syncope (33.3%), palpitations (22.2%), chest pain (22.2%), hemoptysis (11.1%) and constitutional symptoms, including fever (44.4%), fatigue (55.6%) and weight loss (55.6%). Elevated serum inflammatory markers, including an elevated erythrocyte sedimentation rate, lactate dehydrogenase and C‐reactive protein, were recorded in 9 (100%), 7 (77.8%) and 8 (88.9%) patients, respectively. Computed tomography pulmonary angiography (CTPA) indicated that 8 (88.9%) patients had intraluminal defects, appearing as rounded, bulging or lobulated masses that display uneven signal intensification in contract‐enhanced scans in the pulmonary arteries (PAs). Three (33.3%) of the patients had metastases outside of the PA. Before surgery, 7 patients had been misdiagnosed as pulmonary thromboembolic diseases (PTD), 2 as others, with mean misdiagnosis duration of 7.2 ± 7.1 months. All patients had received thrombolytic and/or anticoagulation therapy and their diseases progressed until receiving pulmonary endarterectomy. Conclusions: The clinical features of PAS that may help to differentiate it from PTD are its insidious onset, constitutional symptoms, increased serum inflammatory marker levels, lack of predisposing factors and unresponsiveness to thrombolytic and/or anticoagulation therapy. Typical CTPA features are crucial for suspicion of PAS. Early biopsy or surgery should be performed to confirm the diagnosis of PAS and improve its prognosis.